2008
DOI: 10.2353/ajpath.2008.070778
|View full text |Cite
|
Sign up to set email alerts
|

Trp53 Deletion Stimulates the Formation of Metastatic Pancreatic Tumors

Abstract: The presence of distant metastases is a common finding on diagnosis of pancreatic cancer; however, the mechanisms underlying the dissemination of this tumor type remain poorly understood. Loss of the p53 tumor suppressor protein has been associated with tumor progression and metastasis in several tumor types including pancreatic ductal adenocarcinoma. Here, we describe the generation of a progressive and metastatic pancreatic cancer mouse model after the somatic and sporadic delivery of avian retroviruses enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 29 publications
2
28
3
Order By: Relevance
“…Taken together, our data show that, in a genetic model of human pancreatic cancer in vivo, mutant p53 drives metastasis, most likely by conferring invasive properties on the tumor cells that express it. Our findings differ somewhat from a previous study in which p53 deletion within the pancreas in combination with viral PyMT delivery to elastase-expressing cells led to the formation of metastatic pancreatic cancer (39). In this study, metastases were detected only in animals that developed acinar carcinomas, and these metastatic tumors did not exhibit any ductal characteristics (39).…”
Section: C G and H)contrasting
confidence: 99%
See 1 more Smart Citation
“…Taken together, our data show that, in a genetic model of human pancreatic cancer in vivo, mutant p53 drives metastasis, most likely by conferring invasive properties on the tumor cells that express it. Our findings differ somewhat from a previous study in which p53 deletion within the pancreas in combination with viral PyMT delivery to elastase-expressing cells led to the formation of metastatic pancreatic cancer (39). In this study, metastases were detected only in animals that developed acinar carcinomas, and these metastatic tumors did not exhibit any ductal characteristics (39).…”
Section: C G and H)contrasting
confidence: 99%
“…Our findings differ somewhat from a previous study in which p53 deletion within the pancreas in combination with viral PyMT delivery to elastase-expressing cells led to the formation of metastatic pancreatic cancer (39). In this study, metastases were detected only in animals that developed acinar carcinomas, and these metastatic tumors did not exhibit any ductal characteristics (39). It is therefore likely that the ability of mutant p53 to promote metastasis is influenced by primary tumor type.…”
Section: C G and H)contrasting
confidence: 99%
“…One recent study showed PDX1 to be down-regulated during EMT (David et al 2016). In vivo, metastatic lesions also exhibit loss of nuclear PDX1 expression, further suggesting a possible regulatory role of PDX1 in EMT (Morton et al 2008). Similarly, we found that EMT in PDA attenuates PDX1 expression both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 77%
“…p53 repressed the transcriptional expression of CD44, which is a transmembrane cell-surface protein that promotes tumor growth and metastasis (Godar et al, 2008). Moreover, loss of p53 function enhanced invasion and metastasis in a number of in vivo models of metastatic pancreatic tumors and hepatocellular carcinoma (Lewis et al, 2005;Morton et al, 2008), which suggests that p53 is involved in the regulation of many metastasis-associated genes, which probably include MTA1. p53 facilitates transcriptionally positive or negative regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%